Changes in serum hepatitis B surface and e antigen, interferon‐inducible protein 10, and aminotransferase levels during combination therapy of immune‐tolerant chronic hepatitis B. Issue 3 (14th March 2022) - Perrillo, Robert; Lin, Hsing‐Hua S.; Schwarz, Kathleen B.; Rosenthal, Philip; Lisker‐Melman, Mauricio; Chung, Raymond T.; Prokunina‐Olsson, Ludmila; Coherty, Gavin; Feld, Jordan; ,
Abstract: Background and Aims: Treatment of immune‐tolerant (IT) children and adults with combined peginterferon alfa‐2a and entecavir results in a decline in serum HBeAg and HBsAg concentrations but rarely results in loss of HBeAg or sustained off‐treatment response. Factors associated with declines in these viral antigens during treatment remain unexplored. Approach and Results: We investigated the pattern of virologic and biochemical response in 86 participants (59 children, 27 adults) by serial quantitative measurement of HBsAg (qHBsAg), quantitative HBeAg (qHBeAg), HBV RNA, interferon‐inducible protein (IP‐10), IL‐18, and alanine aminotransferase (ALT). Each individual had previously been treated with 8 weeks of entecavir followed by 40 weeks of combined peginteferon and entecavir. We defined the interrelationships between these parameters and virologic response measured as nadir declines from baseline for HBeAg and HBsAg. The patterns of HBsAg and HBeAg decline were similar in pediatric and adult participants. Higher levels of IP‐10 were observed during treatment in participants with greater ALT elevations and greater reductions of qHBsAg and qHBeAg. Individuals with peak ALT values exceeding three times the upper limit of normal were significantly more likely to have >1 log10 decline in both viral antigens. HBV DNA became undetectable in 21 of 86 (24%) and HBV RNA in 4 of 77 (5%) during therapy, but both markers remained negative only in those who became HBsAg negative, all of whom also had ALT elevations. Conclusions: Induction of IP‐10 during peginterferon treatment in adults and children in the IT phase of chronic HBV infection is associated with ALT elevations and decline in viral antigens, suggesting a degree of interferon‐inducible viral control. Abstract :